Microbiota differences of skin and pharyngeal microbiota between patients with plaque and guttate psoriasis in China - Hu, Jingjin; Lu, Wenhua; Li, Xingyu; Yang, Jing; Tan, Minjia; Hu, Kun; Wang, Qiaolin; Deng, Sichun; Liu, Yijie; Chen, Junchen; Zhu, Wu; Kuang, Yehong (Frontiers in Microbiology, 2022)
Psoriasis can be provoked or exacerbated by environmental exposures such as certain microbiomes. The distinction between plaque psoriasis (PP) and guttate psoriasis (GP) in the skin or pharyngeal microbiota is not yet clear. High-throughput sequencing using Illumina MiSeq was used in this study to characterize skin and pharyngeal microbial composition in patients with PP (large PP (PP, n=62), small PP (SPP, n=41)) and GP (n=14). The alpha and beta diversity of skin microbiota LPP was similar to that of the SPP group, but different from the GP group. There were no differences in pharyngeal microbiota among the groups. According to LEfSe analysis, Staphylococcus, Stenotrophomonas, Enhydrobacter, Brevundimonas, and Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium were the dominant genera of skin microbiota in PP. Diversity of skin microbiota correlated with Psoriasis Area and Severity Index (PASI). Moderate-to-severe psoriasis and mild psoriasis have different microbiota compositions. The skin microbiota may be related to the pharyngeal microbiota. Furthermore, two microbiota models could distinguish psoriasis subtypes with ROC-AUC of 0.935 and 0.836, respectively. In conclusion, the skin microbiota in patients with LPP is similar to that in patients with SPP, but displays variations compared to that of GP, no differences are noted between subtypes in pharyngeal microbiota. Skin microbiota diversity is correlated with PASI.